Correlation between placental thickness in the second and third trimester and fetal weight - Maryam Afrakhteh; Aida Moeini; Morteza Sanei Taheri; Hamid Reza Haghighatkhah (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To investigate relationship between placental thickness during the second and third trimesters and placental and birth weights. METHODS: From January 2011 to June 2012, a total of 250 singleton pregnant women presented at our antenatal clinic were enrolled in this prospective study. All recruited women were assessed at the 1st trimester screening for baseline demographic and obstetric data. The placental thickness was measured trans-abdominally by placing the ultrasound transducer perpendicularly to the plane of the placenta, in the area of the cord insertion at second and third trimester. Pearson's correlation analysis was used to establish the degree of relationship between placental thickness and birth and placental weights. RESULTS: Of 250 recruited participants, 205 women were able to complete the study. The mean age of cases was 26.4±5.1. Values of mean birth and placental weights were 305.56±657.0 and 551.7±104.8 grams respectively. Ultrasonographic measures of placental thickness in second and third trimester and changes between them were 21.68±4.52, 36.26±6.46 and 14.67±5.67 mm respectively. There was a significant positive correlation between placental thickness and birth weight in the second and third trimesters (r=0.15, p=0.03; r=0.14, p=0.04 correspondingly). CONCLUSION: According to our study, birth weight has a positive relation with both second and third trimester placental thickness; however, placental thickness change could not predict low birth weight.